End-tidal CO2 relates to seasickness susceptibility: A study in Antarctic voyages. Issue 5 (October 2017) - Hasegawa, Tatsuhisa; Oe, Hirofumi; Taki, Masakatsu; Sakaguchi, Hirofumi; Hirano, Shigeru; Wada, Yoshiro
Abstract: Objective: To investigate the relationship between end-tidal CO2 (EtCO2 ) and seasickness (motion sickness at sea) during an Antarctic voyage. Methods: In this study, we measured EtCO2 and severity of seasickness using the subjective symptoms of motion sickness (SSMS). We sampled EtCO2 and SSMS every 3–4 h for 3 days from the date of sail in 16 healthy subjects. This experiment was performed on an icebreaker (standard displacement: 12, 650 t). Results: Since 2 subjects dropped out because of severe motion sickness, available data were collected from 14 subjects. On analysis of all data of all subjects grouped together, there seemed to be a significant negative correlation between EtCO2 and SSMS ( R  = −0.27, P  = 0.0005). However, in individual subjects, this correlation was not obvious. During the voyage, EtCO2 level in the seasickness susceptible group was lower than that in the non-susceptible group ( P  = 0.018). Both EtCO2 increasing in the non-susceptible group and decreasing in the susceptible group contribute to the difference in EtCO2 levels. We suggest that the cause of this increase in EtCO2 level in the non-susceptible group was unwitting slow and deep breathing to resist seasickness. Conclusion: We revealed that for seasickness during an Antarctic voyage, EtCO2 level relates to susceptibility, but not occurrence or severity. Measurement of EtCO2 levels may be useful to identify seasickness-susceptible persons and to efficiently prevent seasickness.